MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA KELAS XI IPA DENGAN PENERAPAN PEMBELAJARAN KOOPERATIF STAD MATERI LIMIT FUNGSI DI SMAN 1 KURIPAN - Baiq Sri Herlina Muliati (FKIP Universitas Mataram, 2023)
ABSTRACT The purpose of this research is to increase the students’ learning activeness and achievment trought the implementation of STAD cooperative learning on limit function at XIth grade IPA 2 SMAN 1 Kuripan in the academic year of 2021/2022. The kind of this research was a classroom action research (CAR) which was conducted in two cycles. Each cycle includes planning, acting, observation, evaluation and reflection. The research subjects were the students of XIth grade IPA 2 consisting of 25 students; 14 females and 11 males. The result showed that students’ activeness scores in cycle I for each meeting were 9,33 and 9,98 categorized less active and active, while in the cycle II for each meeting were 10.33, and 10.66 categorized as active . The everage score was 66.2 and the presentage of classical completeness was 68% for the cycle I and the everage score was 70.88 and the presentage of classical completeness was 80% for the cycle II. The conclusion was the implementation of STAD learning could increase the students’ learning activeness and achievement on limit funtion at XIth grade IPA 2 SMAN 1 Kuripan in the academic year of 2021/2022.